Piperazine and piperidine‐substituted 7‐hydroxy coumarins for the development of anti‐inflammatory agents. Issue 7 (22nd March 2021) - Buran, Kerem; Reis, Rengin; Sipahi, Hande; Önen Bayram, F. Esra
Abstract: Coumarins (2 H ‐1‐benzopyran‐2‐one), derivatives that can be isolated from several plants, have been reported for their anticoagulant, antimicrobial, anti‐inflammatory, or anticancer activity. Some of these structures are currently approved for the treatment of cardiovascular diseases, as antibiotics or as an anticancer drug. Given the great potential of this structure and the limited number of studies that focus on molecules derived from carbon 8 of the benzopyranone heterocycle, we synthesized in this project 38 coumarin derivatives by substituting carbon 8 of the benzopyran ring with some aromatic and aliphatically substituted piperidines and piperazines. As a few of these structures were already shown to exhibit some carbonic anhydrase (CA) inhibition and as CA enzymes are reported to be closely related to inflammation, the synthesized derivatives were evaluated for their anti‐inflammatory activity in vitro. The results indicated that compounds 20 and 31 revealed promising anti‐inflammatory activity, as they demonstrated better activity than the reference drugs. Abstract : A series of 38 coumarin (2 H ‐1‐benzopyran‐2‐one) derivatives was synthesized by substituting carbon 8 of the benzopyran ring with aromatic and aliphatically substituted piperidines and piperazines. The synthesized derivatives were evaluated for their anti‐inflammatory activity in vitro. The highest anti‐inflammatory activities (nitrite inhibition) were observed for compounds 20 and 31 . Compounds 24 and 25 also led to a slight decrease in prostaglandin E2 synthesis.